Blood Feeding Insect Series: Yellow Fever - Walter J. Tabachnick; C. Roxanne Rutledge-Connelly; Christopher N. Mores; Chelsea T. Smartt (EDIS)
ENY-732, a 3-page illustrated fact sheet by Walter J. Tabachnick, C. Roxanne Connelly, Christopher N. Mores, and Chelsea T. Smartt, describes this feared human disease transmitted through the bite of infected mosquitoes, which even today poses formidable challenges and dangers to humans around the world. Includes history, description of the disease, the virus, and insect transmission, the importance of yellow fever today, and suggested further reading. Published by the UF Department of Entomology and Nematology, November 2006.